Pengaruh Capital Intensity, Leverage dan Company Size Terhadap Tax Avoidance pada Perusahaan Subsektor Property dan Real Estate yang Terdaftar di BEI - Jumyati, Jumyati; Huda, Nurul; Muniarty, Puji (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to analyze the effect of capital intensity, leverage, and company size on tax avoidance in property and real estate sub-sector companies listed on the Indonesia Stock Exchange (IDX) during the 2019–2023 period. The research method used is an associative quantitative approach with secondary data obtained from corporate financial reports. The sample was selected using purposive sampling technique, resulting in 4 companies that met the criteria. The multiple linear regression analysis shows that partially, capital intensity and leverage have a significant positive effect on tax avoidance, while company size has a significant negative effect. Simultaneously, the three variables have a significant influence on tax avoidance. This study implies that companies should consider fixed asset investment strategies, financing structure, and firm size in managing their tax obligations efficiently and legally.